Ultrasound assessment of fetal biometry in Iranian normal pregnancies - Mahboobeh Shirazi; Shirin Niroomanes; Fatemeh Rahimi; Fatemeh Golshahi (International Journal of Preventive Medicine, 2019)
Background: The objective of this study was to provide biometric charts for Iranian fetuses. Methods: One thousand four hundred and twenty-two women enrolled. Four hundred and eighty-four were in the second trimester of pregnancy and 940 were in the third trimester. Data were presented as mean ± standard deviation for continuous variables. Percentiles (5th, 50th, 75th, and 90th) reported. Results: Mean femoral length ranged from 16 to 53 mm in our study in the second trimester and 55–79 mm in the third trimester. Mean biparietal diameter (BPD) for fetuses with in the second trimester was between 14 and 71 and for fetuses in the third trimester was between 74 and 98 mm. Mean abdominal circumference (AC) in our cases with gestational age between 14 and 41 ranged between 86 and 365 mm. Conclusions: We have provided normal reference ranges and percentiles for BPD, AC, femur length, and weight during the second and third trimester of pregnancy in an Iranian population.